Phenotypic clusters and survival analyses in interstitial pneumonia with myositis-specific autoantibodies - Li, Yihua; Fan, Yali; Wang, Yuanying; Yang, Shuqiao; Du, Xuqin; Ye, Qiao (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Interstitial pneumonia (IP) is one of the common pulmonary complications of idiopathic inflammatory myopathy (IIM), among which myositis-specific autoantibodies (MSAs) are specific for diagnosing and predicting the prognosis of IIM. Objectives: The study aimed to explore the phenotypic clusters and prognosis of patients with IP and MSA (MSA-IP). Methods: A total of 178 patients with MSA-IP were prospectively enrolled for analysis. Serum MSAs were detected using Western blotting. Radiological patterns of IP were determined according to the classification of idiopathic IPs. Clusters of patients with MSA-IP were identified using cluster analysis. Predictors for acute/subacute onset, therapeutic response, IP progression and survival were also analyzed. Results: Patients with MSA-IP were classified into four distinct clusters. Cluster 1 were the elderly with chronic onset, nearly normal oxygenation and good survival. Cluster 2 had dyspnea on exertion and nonspecific IP pattern, with moderate survival. Patients in cluster 3 had chronic onset and were prone to IP progression (OR 2.885). Cluster 4 had multi-systemic involvements, positive anti–melanoma differentiation associated gene 5 antibody, and were prone to acute/subacute onset (OR 3.538) and IP progression (OR 5.472), with poor survival. Corticosteroids combined immunosuppressants showed therapeutic response in MSA-IP (OR 4.303) and had a protective effect on IP progression (OR 0.136). Conclusions: Four clusters of the patients with MSA-IP suggested the distinct clinical, radiological and prognostic features.